Historical Development of the Concept of Gender Equality in Employment Relationships - Rakhmanova Sabrina (Periodica Journal, 2023)
Gender equality is a key principle of modern society, aiming for fair and equitable development. In the context of employment relationships, it plays a crucial role in ensuring equal opportunities and rights for men and women in the workplace. This article examines the historical development of the concept of gender equality in employment relationships in the Republic of Uzbekistan and globally. It highlights important milestones and provides practical recommendations for further advancement
Keywords: relationships; Republic of Uzbekistan; historical